2013
DOI: 10.3892/or.2013.2600
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis lipopolysaccharide increases lipid accumulation by affecting CD36 and ATP-binding cassette transporter A1 in macrophages

Abstract: Porphyromonas gingivalis lipopolysaccharide (P. gingivalis LPS) promotes macrophage-derived foam cell formation, however, the mechanisms are not well established. In macrophages, lipid uptake is mediated by scavenger receptors including SR-A and CD36, while the cholesterol efflux is mediated by ATP-binding cassette transporter G1 (ABCG1), ABCA1 and SR-BI. We further investigated the mechanisms underlying the dysregulation by P. gingivalis LPS of these regulators resulting in the promotion of lipid accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…We tested our hypothesis that SFA, which is rich in the HFD used in our animal study and involved in the pathogenesis of MetS (Phillips et al , ), acts with LPS to upregulate CD36 expression in macrophages. The finding from this study supports our hypothesis as it showed that while either palmitate or LPS‐stimulated CD36 expression, which is in agreement with the previous reports (Chabowski et al , ; Li et al , ; Pararasa et al , ), the combination of palmitate and LPS stimulated CD36 expression to a higher level. As it is known that SFA is increased in MetS patients (Rivellese et al , ; Tuomilehto, ) and MetS mice (Morselli et al , ), and LPS is increased in patients with periodontitis, palmitate and LPS are likely to act in concert to stimulate CD36 expression in patients or mice with both MetS and periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…We tested our hypothesis that SFA, which is rich in the HFD used in our animal study and involved in the pathogenesis of MetS (Phillips et al , ), acts with LPS to upregulate CD36 expression in macrophages. The finding from this study supports our hypothesis as it showed that while either palmitate or LPS‐stimulated CD36 expression, which is in agreement with the previous reports (Chabowski et al , ; Li et al , ; Pararasa et al , ), the combination of palmitate and LPS stimulated CD36 expression to a higher level. As it is known that SFA is increased in MetS patients (Rivellese et al , ; Tuomilehto, ) and MetS mice (Morselli et al , ), and LPS is increased in patients with periodontitis, palmitate and LPS are likely to act in concert to stimulate CD36 expression in patients or mice with both MetS and periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…The role of SRA and CD36 in recognition and internalization of modified lipoproteins has been extensively studied [20]. However, the role of TLRs, the major receptors that detect and respond to bacteria and its product, has been less studied in the inflammatory response to oxLDL.…”
Section: Discussionmentioning
confidence: 99%
“…Such autoantibodies can be induced in response to bacterial epitopes — such as those found in P. gingivalis arginine-specific gingipains and T. denticola phosphoglycerate kinase — that bear homology to the TLRVYK peptide of the phospholipid-binding serum protein β2-glycoprotein-I 119,120 . Furthermore, P. gingivalis enhances low-density lipoprotein-uptake and foam cell formation by upregulating CD36 (a scavenger receptor mediating lipid uptake) and downregulating ATP-binding cassette transporter A1 (which mediates the efflux of cholesterol from macrophages) 121,122 . In a similar context, the pathogen induces vascular smooth-muscle-cell proliferation leading to neo-intima formation, and stimulates production of matrix metalloproteinases that contribute to plaque rupture and thrombotic vessel occlusion 6 ( FIG.…”
Section: Periodontitis and Cardiovascular Diseasementioning
confidence: 99%